Lard Vader's villains - Amos, Ruth (London : Dorling Kindersley, 2013)
Discover a band of naughty villains! Meet Lard Vader and the Empire pigs as they try to take control of the galaxy.
Includes index.
Keywords: Children's stories; Science fiction